The Role of Agricultural Instructors on Coffee Farmers’ Technical Capabilities - Ulhaq, Afifah; Harpowo, Harpowo; Erni Widyastuti, Dyah (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021, 2021)
Improving farmers' skills is one of the objections of extension program. Agricultural instructors through extension programs help farmers in the implementation of agricultural commodities according to the procedure. The aim of this study was to determine the technical capabilities of coffee farmers, the role of agricultural extension instructors as motivators, educators, facilitators, communicators and dynamists as well as the influence of the role of agricultural extension instructors on the technical abilities of coffee farmers. The quantitative descriptive method was used in this study. The object of research was the “Tani Harapan” Farmer Group in Amadanom Village, Dampit District, Malang Regency. Census was held for the determination of respondents. Primary data were collected by means of observation, interviews, and questionnaires. Analysis of the data used was Multiple Linear Regression. The results of the study explained that the role of agricultural extension was included in the category often done with a percentage of 39.40% and the technical abilities of farmers included in the category of very capable with a percentage of 88.48%. The role as educator and facilitator has a positive effect while the motivator, communicator and dynamicator does not affect the technical ability of coffee farmers. The successful implementation of the instructor's role experienced obstacles caused by age factors. The age of the members of the farmer group is not productive, and therefore often has difficulty in understanding the material and practices provided by the instructors.